(untitled) (Prosiding dan Call Paper Widya Wiwaha, 2023)
This study examines village heads in PBB-P2 literacy in Pamekasan District. This study was conducted using a qualitative method with a phenomenological approach, the samples from this study were Village X and Village Y. Data analysis was carried out using transcendental phenomenology which focused on subjective awareness studies through in-depth interviews. The results of subjective in-depth interviews will be set forth in working papers or in the form of tables which include noema, noesis, epoche (bracketing), intentional analysis, and eidetic reduction. The results of the analysis show that there are differences in the collection method between Village X and Village Y, where in Village X it is carried out through the village treasurer, meaning that all PBB-P2 belonging to the Village X community is directly implemented by the village head. Whereas in Y Village it was carried out through the hamlet head as an officer appointed by the village head to collect PBB-P2 directly from the community, meaning that there was socialization and education regarding awareness of taxpayers in Y Village to pay taxes.